ANALISIS PENERAPAN PROSEDUR KESELAMATAN KERJA PADA PROSES TANK CLEANING DI KAPAL MT. GERALDINE - Muhammad Alfian Antariksa; Eva Susanti; Indra Farman (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The background of this study is based on the existence of non compliance in the implementation of work safety procedures during the tank cleaning process on MT. Geraldine, especially in entering cargo tanks before the tank condition was declared safe based on gas measurement results. This condition may increase the risk of work accidents such as gas poisoning, oxygen deficiency, and explosions caused by hydrocarbon vapors. This study aims to analyze the implementation of work safety procedures during the tank cleaning process and identify the factors causing the lack of crew compliance with safety procedures. This research used a qualitative approach with data collection techniques through observation, interviews, and documentation during sea practice on board MT. Geraldine. The research informants consisted of the Chief Officer, Second Officer, Bosun, Able Seaman (AB), and Pumpman. Data analysis techniques used the Miles, Huberman, and Saldaña model, including data reduction, data presentation, and conclusion drawing supported by NVivo 12 software. The results showed that the implementation of work safety procedures during the tank cleaning process on MT. Geraldine had not been carried out optimally. The non-compliance with procedures was influenced by operational time pressure, lack of crew understanding of work hazards, weak supervision, and ineffective safety meetings. Efforts that can be made include improving the quality of safety meetings, conducting regular safety training, strengthening supervision, and increasing crew awareness of the importance of complying with work safety procedures in accordance with ISM Code and ISGOTT standards.